Clinical, Paraclinical Characteristics and Relative Risk Factors of Severe Degree in Children with COVID-19: Systematic Review - Van Dem, Pham; Trung Kien, Pham; Thanh Trung, Nguyen; Thu Huong, Nguyen; Thanh Nam, Nguyen; Quang Tue, Pham; Minh Dien, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 1, 2022)
Aim: systematic review of studies in the medical literature of children with COVID – 19 in order to provide evidence of clinical, paraclinical characteristics and relative risk factors of severe degree in children with COVID-19. Research subjects: A systematic review of studies on COVID-19 in children published in the international medical literature. Research methods: the information of research reports was selected from information posted on the COVID-19 update reporting portal of the Ministry of Health, PubMed, EMBASE, Cochrane Library, WHO COVID-19 Database, China National Knowledge Infrastructure (CNKI) Database, WanFang Database through system overview. Results: we collected 115 studies related to COVID-19 in children, published from January 2020 to August 2021, and by screening, we selected 21 studies related to clinical, paraclinical characteristics and relative risk factors of severe degree in children with COVID-19. Keywords: Variant Delta, COVID-19 in children, Clinical, Paraclinical Characteristics and risk factors of severe degree. References [1] Minnistry of Health, Dayly Recorded of COVID-19 (in Vietnamese), https://www.moh.gov.vn/ (accessed on: August 31st, 2021). [2] World Health Organization, Clinical Management Severe Acute Respiratory Infection when Novel Coronavirus (2019-nCoV) Infection is Suspected: Interim Guidance, 2020, 28 January 2020, pp. 1-10. [3] CDC (Centers for Disease Control and Prevention), COVID-19 Response Team, Coronavirus Disease 2019 in Children-United States, February 12-April 2, 2020, MMWR Morb Mortal Wkly Rep, 2020, Vol. 69, No, 14, pp. 422-426, https://doi.org/10. 15585/mmwr.mm6914e4. [4] J. F. Ludvigsson, Systematic review of COVID-19 in Children Shows Milder Cases and a Better Prognosis than Adults, Acta Paediatr, 2020 Jun, Vol. 109, No. 6, pp. 1088-1095, https://doi.org/10.1111. [5] CDC (Centers for Disease Control and Prevention), US COVID-19 Cases caused by Variants, Up-to-Date Info: https://www.cdc.gov/coronavirus/2019-nCoV (accessed on: August 31st, 2021). [6] N. Parri, M. L. D. Buonsenso, Children with Covid-19 in Pediatric Emergency Departments in Italy, N Engl J Med, 2020, Vol. 383, No. 2, pp. 187-190, https://doi.org/10.1056/NEJMc2007617, 2020. [7] Q. Lu and Y. Shi, Coronavirus Disease (COVID-19) and Neonate: what Neonatologist Need to Know, J Med Virol, 2020, Vol. 92, No. 6 , pp. 564-567, https://doi.org/10.1002/jmv.25740. [8] H. Tezer and T. B. Demirdrag, Novel Coronavirus Disease (COVID-19) in Children, Turk J Med Sci, 2020, Vol 50, pp. 592-603, https://doi.org/10.3906/sag-2004-17, 2020. [9] L. K. Zeng, X. W. Tao, W. H. Yuan et al., First Case of Neonate Infected with Novel Coronavirus Pneumonia in China. Front. Pediatr, 2020, Vol. 8, pp. 1-8, https://doi.org/10.3389/fped.2020.00287. [10] M. Wei, J. Yuan, Y. Liu et al., Novel Coronavirus Infection in Hospitalized Infants Under 1 Year of Age in China. JAMA, 2020, Vol. 323, No. 13, pp. 1313-1314, https://doi.org /10.1001/jama.2020.2131. [11] D. Wang, X. L. Ju, F. Xie et al., Clinical Analysis of 31 Cases of 2019 Novel Coronavirus Infection in Children from Six Provinces (Autonomous Region) of Northern China, Zhonghua Er Ke Za Zhi, 2020, Vol. 58, No. 4, pp. 269-274, https://doi.org/10.3760/cma.j.cn112140-20200225-00138, 2020. [12] S. Tiana, N. Hub, J. Lou et al., Characteristics of COVID-19 Infection in Beijing, J Infect, 2020, Vol. 80, No. 4, pp. 401-406, https://doi.org/10.1016/j.jinf.2020.02.018. [13] H. Zhu, L. Wang, C. Fang et al., Clinical Analysis of 10 Neonates Born to Mothers with 2019-nCoV Pneumonia. Transl Pediatr, 2020, Vol. 9, pp. 51-60, https://doi.org/10.21037/tp.2020.02.06. [14] Y. Dong, X. Mo, Y. Hu et al., Epidemiological Characteristics of 2143 Pediatric Patients with 2019 Coronavirus Disease in China, J Emerg Med, 2020, Vol . 58, No. 4, pp. 712-713, https://doi.org/1016/j.jemermed.2020.04.006. [15] I. Liguoro, C. Pilotto, M. Bonann et al., SARS-COV-2 Infection in Children and Newborns: A Systematic Review. SARS-COV-2 Infection in Children and Newborns: A Systematic Review, European Journal of Pediatrics, 2020, Vol. 18, 2020, pp. 1-18, https://doi.org/10.1007/s00431-020-03684-7. [16] J. Yasuhara, T. Kuno, H. Takagi, Clinical Characteristics of COVID‐19 in Children: A Systematic Review, Pediatric Pulmonology, 2020, Vol. 55, No. 10, pp. 2565-2575, https://doi.org/10.1002/ppul.24991. [17] T. H. D. Souza, J. A. Nadal, R. J. N. Nogueira et al., Clinical Manifestations of Children with COVID-19: A Systematic Review, Pediatr Pulmonol, 2021, Vol. 55, No. 8, pp. 1892-1899, https://doi.org/ 10.1002/ppul.24885. [18] Q. Shen, W. Guo, T. Guo et al., Novel Coronavirus Infection in Children Outside of Wuhan, China, Pediatr Pulmonol, 2020, Vol. 55, No. 6, pp. 1424-1429, https://doi.org/10.1002/ppul.24762. [19] H. Qiu, J.a Wu, L. Hong et al., Clinical and Epidemiological Features of 36 Children with Coronavirus Disease 2019 (COVID-19) in Zhejiang, China: an Observational Cohort Study, Lancet Infect Dis, 2020, Vol. 20, No. 6, pp. 689-696, https://doi.org/10.1016/S1473-3099(20)30198-5. [20] N. M. Mustafaa, L. A. Selimc, Characterisation of COVID-19 Pandemic in Paediatric Age Group: A Systematic Review and Meta-Analysis, J Clin Virol, 2020, Vol. 128, pp. 1-15, https://doi.org/10.1016/j.jcv.2020.104395. [21] W. Guan, Z. Y. Ni, Y. Hu et al., Clinical Characteristics of 2019 Novel Coronavirus Infection in China, 2020, N Engl J Med, Vol. 382, pp. 1708-1720, https://doi.org/10.1056/NEJMoa2002032.